Primeira ocorrência de Biomphalaria straminea no Sul Goiano, Brasil First occurrence of Biomphalaria straminea in the South Goiano, Brazil - Carlos Henrique Marchiori (Universidade de São Paulo, 1999)
Relata-se a primeira ocorrência do Biomphalaria straminea no Sul do Estado de Goiás, em ambiente natural. Trinta exemplares de Biomphalaria straminea foram coletados em janeiro de 1998, em Cachoeira Dourada de Goiás. Verificou-se que a falta de saneamento e de educação sanitária da população e a presença do caramujo são condições fundamentais para o estabelecimento de um foco de transmissão. The objective of this note is to report the occurrence of the Biomphalaria straminea in the county of Cachoeira Dourada in the south of Goiás, and with that enhance the knowledge about its geographical distribution in the state. More than identify the species, the collection of thirty samples helped study and verify the presence of cercariae, especially because they were found in a setting which offers proper conditions to the development of a focal transmission site of schistosomiasis.